Proceedings of the 40th International Conference on Software Engineering 2018
DOI: 10.1145/3180155.3180193
|View full text |Cite
|
Sign up to set email alerts
|

Do programmers work at night or during the weekend?

Abstract: Abnormal working hours can reduce work health, general wellbeing, and productivity, independent from a profession. To inform future approaches for automatic stress and overload detection, this paper establishes empirically collected measures of the work patterns of software engineers. To this aim, we perform the first largescale study of software engineers' working hours by investigating the time stamps of commit activities of 86 large open source software projects, both containing hired and volunteer develope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…While this includes an average of 44 minutes non-work time spent at lunch and with bio breaks, the time spent at work is nonetheless higher than the often considered 8 hours for a regular workday (e.g. [64]). Since developers at the studied organization can freely organize their work hours, this might be an indication of developers working overtime, an observation that was previously made for German and Finnish workers who had autonomy over their working time and worked overtime [65], [66].…”
Section: Time Spent On Activities At Workmentioning
confidence: 99%
“…While this includes an average of 44 minutes non-work time spent at lunch and with bio breaks, the time spent at work is nonetheless higher than the often considered 8 hours for a regular workday (e.g. [64]). Since developers at the studied organization can freely organize their work hours, this might be an indication of developers working overtime, an observation that was previously made for German and Finnish workers who had autonomy over their working time and worked overtime [65], [66].…”
Section: Time Spent On Activities At Workmentioning
confidence: 99%
“…In the sector of software development, Claes et al [7] investigated the timestamps of commit activities of software projects from Mozilla, Apache and a local Finnish IT company to study developers' working hours. They found that two-thirds of the developers typically worked from 10 a.m. to 6 p.m. and did not work during nights and weekends very often.…”
Section: Related Workmentioning
confidence: 99%
“…To investigate the situations of overtime work, first we need to determine working hours of the companies. We follow Claes et al's method [7]. Companies are assumed to follow an eight-hour work schedule on work days.…”
Section: Insights Of Working Overtime In It Companiesmentioning
confidence: 99%
See 2 more Smart Citations